Data structures and algorithms in java - Goodrich, Michael T.; Tamassia, Roberto , 1960- (John Wiley & Sons, 2011)
In this updated fifth edition, software engineers will find accessible coverage of fundamental data structures using a consistent object-oriented framework. The discussions throughout the book now feature the latest information on Java JDK 1.6